Secondary infection of Fasciola gigantica in buffaloes shows a similar pattern of serum cytokine secretion as in primary infection - Meng, Zhen; Zhai, Lele; Guo, Yanfeng; Zheng, Mengwei; Li, Liang; Wen, Chongli; Zhang, Weiyu; Di, Wenda (Frontiers in Veterinary Science, 2023)
Background: As a natural host of Fasciola gigantica, buffalo is widely infected by F. gigantica. Its impact on buffalo production has caused great losses to the husbandry sector, and repeat infection is non-negligible. In buffaloes experimentally infected with F. gigantica, primary and secondary infection have yielded the same rate of fluke recovery, indicating a high susceptibility of buffalo to F. gigantica, which contributes to the high infection rate. Determining the immunological mechanism of susceptibility will deepen the understanding of the interaction between F. gigantica and buffalo. Here, we explored the immune response of buffaloes against primary and secondary F. gigantica infection, with a focus on cytokines’ dynamics explored through serum cytokine detection. Methods: Buffaloes were assigned to three groups: group A (noninfected, n = 4), group B (primary infection, n = 3), and group C (secondary infection, n = 3). Group B was infected via oral gavage with 250 viable F. gigantica metacercariae, and group C was infected twice with 250 metacercariae at an interval of four weeks. The second infection of group C was performed simultaneously with that of group B. Whole blood samples were collected pre-infection (0 weeks) and at 1–6, 10, and 12 weeks after that. The serum levels of seven cytokines (interferon IFN-γ, IL-4, IL-5, IL-10, IL-13, transforming growth factor [TGF]-β, and IL-17) were simultaneously determined using ELISA and further analyzed. Results: In the present study, no significant changes in Th1-type cytokines production were detected in early infection, both in primary and secondary infections, while the Th2-type response was strongly induced. A comparison of primary and secondary infection showed no significant difference in the cytokine secretion, which may indicate that the re-infection at four weeks after primary infection could not induce a robust adaptive immune response. The full extent of interaction between buffalo and F. gigantica in re-infection requires further study.